Perkembangan Baitul Maal pada Masa Rasulullah hingga Era Modern - Muqsith, Ariel; Sulastri (Al-fiqh, 2025)
This research is a form of study of Baitul Maal during its inception to its application in the modern era. Baitul Maal is a financial institution that has a role in collecting, managing, and distributing assets and social funds for the community / people who are entitled to receive them. These assets are also used as a state treasure. This research is a literature review with a qualitative analysis method. To get data sourced from journals and other scientific papers. The results obtained for this research are about the history of Baitul Maal from the time of its presence at the time of the Prophet Muhammad, where the Prophet Muhammad became the authorized party for the awareness of the people to collect and channel their assets to be managed and distributed. Furthermore, during the Khulafaur Rasyidin period, Baitul Maal became the main supporter in the field of economy and state finances. And in the modern era, Baitul Maal became an inspiration and then applied to banking and non-banking activities as a Muslim awareness of the importance of zakat and equitable / fair public welfare.